The economic impact and performance of irrigation in Zimbabwe - Makombe, Godswill, author; Sampath, R. K., advisor; Davies, S. P., committee member; Dalsted, N., committee member; Fan, L. S., committee member (Colorado State University. Libraries, 2000)
This dissertation addresses some issues concerning the performance of irrigation in Zimbabwe. Experts agree that there are many places in the world, Zimbabwe included, where food supply could better match demand through increased production. One way of increasing food production is through the development of water resources for irrigation. In this study the benefits of irrigation are estimated for maize production in Zimbabwe. A Marshalian partial equilibrium analysis is used to estimate the net benefits for consumers and producers in maize production. The study concludes that the net benefits are high for a strategy that pursues the development of smallholder irrigation as opposed to one that develops large-scale commercial systems. Smallholder irrigation performance in Zimbabwe is assessed in terms of water management and financial performance. The conclusion from the study suggests that smallholder irrigation is a viable development alternative. Smallholder irrigation is defined as the formal systems namely the government managed Agritex systems, the farmer managed community systems and the parastatal supported ARDA outgrowers. This study compares the performance of the formal systems themselves and then the formal systems are compared to the informal bani system. Because of lack of data the ARDA systems are only included in very few of the analyses. The informal bani system is discouraged by the government through statutory instruments. The main conclusions from the performance of the formal systems is that the farmer managed community system outperforms the government managed system in terms of water management and financial performance. To this extent, the government should utilize the farmer-managed model for further smallholder irrigation development. The study also concludes that the informal bani system, which is discouraged by the government, can achieve the objectives of irrigation in much the same way, if not better than the formal systems. However, since there is legislation that discourages the utilization of this resource, it is recommended that the government reviews the legislation, in light of contemporary knowledge, in order to allow this apparently valuable resource to contribute to agricultural development in Zimbabwe.
Keywords: irrigation; studies; land area; livestock; agricultural production; statistical data; food; water shortages; estimates; corn; population density; crops; cattle; agriculture; farmers; farms; copyright; rain